Medinilla madagascariensis, a replacement name for Medinilla albiflora H.Perrier (Melastomataceae) and its lectotypification - Kottaimuthu, Ramalingam; Basu, Muthuramalingam Jothi (Phytotaxa, 2021)
N/A